Microbial hydrolysis of acetylated nucleosides - Panero, Julieta; Trelles, Jorge Abel; Rodano, Valeria; Montserrat, Javier Marcelo; Iglesias, Luis Emilio; Lewkowicz, Elizabeth Sandra; Iribarren, Adolfo Marcelo (Biotechnology Letters)
Enzymatic hydrolysis of acetylated nucleosides using microbial whole cells has been carried out for the first time. Unlike Candida antarctica B lipase-catalysed alcoholysis, none of the tested microorganisms displayed a common deacetylation profile. Depending on the substrate and the biocatalyst used, 5′-selective deprotection or mixtures of mono O-acetylated products were obtained. Fil: Panero, Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Quilmes; Argentina Fil: Trelles, Jorge Abel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Quilmes; Argentina Fil: Rodano, Valeria. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular "Dr. Héctor N. Torres"; Argentina Fil: Montserrat, Javier Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular "Dr. Héctor N. Torres"; Argentina. Universidad Nacional de General Sarmiento. Instituto de Ciencias; Argentina Fil: Iglesias, Luis Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Quilmes; Argentina Fil: Lewkowicz, Elizabeth Sandra. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Quilmes; Argentina Fil: Iribarren, Adolfo Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular "Dr. Héctor N. Torres"; Argentina